2014
DOI: 10.3390/en7128535
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Design Optimization of a Coaxial Surface-Mounted Permanent-Magnet Magnetic Gear

Abstract: This paper presents the analysis and design optimization of a coaxial surface-mounted permanent-magnet magnetic gear. The magnetic field distribution in the coaxial magnetic gear is calculated analytically in the polar coordinate system and then validated by the finite element method (FEM). The analytical field solution allows the prediction of the magnetic torque, which is formulated as a function of design parameters. The impacts of key design parameters on the torque capability are then studied and some sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Research in magnetic gearing has increased in the last 10 years because of its potential for efficient transmission torque, lubrication free maintenance, overload protection and non-contact operation compared to problems of mechanical gears [1]. Studies [2][3][4][5][6][7] have shown that magnetic gears can reach a torque density of 100 kNm/m 3 and by integrating a magnetic gear with a PM machine; the resultant magnetic geared machine can be applied in low-speed high torque applications such as traction motors and as generators in low-speed renewable energy power generation [8,9]. Reference [10] reported that a double-stator PM machine achieved a higher torque density much greater than a single-stator PM machine.…”
Section: Introductionmentioning
confidence: 99%
“…Research in magnetic gearing has increased in the last 10 years because of its potential for efficient transmission torque, lubrication free maintenance, overload protection and non-contact operation compared to problems of mechanical gears [1]. Studies [2][3][4][5][6][7] have shown that magnetic gears can reach a torque density of 100 kNm/m 3 and by integrating a magnetic gear with a PM machine; the resultant magnetic geared machine can be applied in low-speed high torque applications such as traction motors and as generators in low-speed renewable energy power generation [8,9]. Reference [10] reported that a double-stator PM machine achieved a higher torque density much greater than a single-stator PM machine.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 10 years, research in magnetic gears has increased because of their potential for efficient high torque transmission, inherent overload protection, lubrication-free operation and lower acoustic noise when compared with mechanical gearboxes [2]. Also various types of magnetic gears such as coaxial magnetic gears [3,4], linear magnetic gears [5] and axial magnetic gears [6,7] have been proposed and reported to have a transmitted torque density greater than 100 kNm/m 3 . The coaxial magnetic gear concept seems to have attracted much attention because of their good utilization of PMs and high transmission torque density.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, magnetically geared (MG) machines have attracted much attention [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. MG machines incorporate a PM brushless machine and a magnetic gear into one volume.…”
Section: Introductionmentioning
confidence: 99%